Prevalence of Salmonella spp. in poultry carcasses samples collected in slaughterhouses of Southern Brazil from 2006 to 2015 - Mateus Silva de Lima; Leonardo Werlang Isolan; Claudia Titze Hessel; João Pedro Pessoa; Eduardo Cesar Tondo (Journal of Infection in Developing Countries)
Introduction: This study aimed to evaluate the prevalence of Salmonella on poultry carcasses produced in slaughterhouses of Southern Brazil participating of the Official Pathogen Reduction Program conducted by the Ministry of Agriculture, Livestock, and Supply.